PENERAPAN MODEL PEMBELAJARAN INQUIRY TRAINING UNTUK MENINGKATKANAKTIVITAS BELAJAR FISIKA SISWA DI KELAS XI IPA 2 SMA NEGERI 12 MEDAN - NELPI NURSAIDA SINAGA (Universitas Negeri Medan, 2014)
ABSTRACT The objective of research to view the student learning activity which encompass student learning activity while doing in grouping in class on subject Physics lesson which delivered on the students’ learning outcomes increasing by applicated the learning model of Inquiry Training. This subject of research was taken in class of XI IPA 2 SMA Negeri 12 Medan by number of 45 students.The initially of teaching – learning process is done by learning outcomes testing ( Pretest), by the average data is 20,53, it is shown that the students’ average not yet have preparation before learn in the school. Then, continued the teaching – learning process, in the end of second teaching – learning process and the fourth teaching – learning process is done the first formative and second formative of learning outcomes testing, the result is shown that the average of first outcome is 67,91 by the classical completeness is 60% and the second of the average is 89,47 by the classical completeness is 86,66%. By viewing the changing, the changing is effected by the teacher action during teaching – learning process in cycle II. The students’ activities accord the observer viewing on cycle I among others writing / reading (38%), doing worksheet in discuss (22%), asking for friend (17%), asking for teacher (10%), and not relevant with teaching – learning process (13%). The student activities data accord the observation in cycle II among others writing / reading (27%), doing worksheet (31%) , asking for friend (27%), asking for teacher (10%), and not relevant with teaching – learning process (4%). Keywords: Inquiry Training of Learning Model, Students’ activity, the student learning outcomes